1997
DOI: 10.1051/apido:19970606
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and daily variation of honeybee dancing temperature under constant feeding conditions

Abstract: Summary — The seasonal and daily variation of the thorax temperature of dancing honeybee foragers, which gathered sucrose solutions from feeding places of constant quality (concentration and distance), was investigated by infrared thermography. Dancing temperature varied significantly between different days of the foraging season and depended on the time of day. In the morning and evening it varied much more than during the rest of the day. Part of this variation was caused by the hive temperature. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Physiologically, a bee's thoracic temperature depends on her metabolic rate (Moffatt, 2001), which increases with increasing sugar concentration and reward rate at a food source (Moffatt and Núñez, 1997), and also with her motivational state (Balderrama et al, 1992;Moffatt, 2000;Sadler and Nieh, 2011). Although honey bees are capable of detecting temperature differences as small as 0.25°C (Heran, 1952), it is unlikely that dance followers use thoracic temperature as a source of information on the excitement of the dancers (Germ et al, 1997). Even so, hive bees have been shown to adjust their activity level (measured as thoracic temperature) according to that of the foragers (Farina and Wainselboim, 2001), which indicates that bees are indeed capable of perceiving the motivation level of others.…”
Section: The Recruitersʼ Excitement -Reflecting the Motivational Statmentioning
confidence: 99%
“…Physiologically, a bee's thoracic temperature depends on her metabolic rate (Moffatt, 2001), which increases with increasing sugar concentration and reward rate at a food source (Moffatt and Núñez, 1997), and also with her motivational state (Balderrama et al, 1992;Moffatt, 2000;Sadler and Nieh, 2011). Although honey bees are capable of detecting temperature differences as small as 0.25°C (Heran, 1952), it is unlikely that dance followers use thoracic temperature as a source of information on the excitement of the dancers (Germ et al, 1997). Even so, hive bees have been shown to adjust their activity level (measured as thoracic temperature) according to that of the foragers (Farina and Wainselboim, 2001), which indicates that bees are indeed capable of perceiving the motivation level of others.…”
Section: The Recruitersʼ Excitement -Reflecting the Motivational Statmentioning
confidence: 99%
“…Foragers were counted each 15·min and excess foragers were captured in aspirators and released at the end of the day. Germ et al (1997) recommends that honeybee thermal studies be avoided in the early morning or later afternoon to reduce daily climactic variability. Sunrise and sunset times at our field site were approximately 06:00·h and 18:30·h, respectively, throughout our field seasons, and we typically conducted experiments between 10:00·h and 15:00·h.…”
Section: J C Nieh and D Sánchez Foraging Meliponine Thoracic Tempementioning
confidence: 99%
“…Germ et al (1997) reported finding no correlation between honeybee recruitment rates and dancing temperature and thus concluded that thermal information was unlikely to be a primary source of information about food quality. Seeley and Towne (1992) found no evidence that recruiters dancing for a better food source attracted more dance followers than those dancing for a poorer food source.…”
Section: Conspicuousness and Potential Signallingmentioning
confidence: 99%
“…During a foraging trip the challenge is especially high because not only the ambient temperature but also solar radiation may vary in a broad range within a day and during a foraging season [4] , [8] , [9] . In order to assess the energetic demand of foraging bees under variable ambient temperatures there have been measurements of metabolism in the shade, both at artificial flowers [10] – [14] , and during flight [15] [17] .…”
Section: Introductionmentioning
confidence: 99%